Strategy for Strengthening the Non-Communicable Disease Posbindu Program in Klungkung Village, Sukorambi District - Dicky Setiadi Pradana; Susi Wahyuning Asih; Rodhistya Athoillah; Pingki Wahyu Novelya; Sinta Aini Khoiriyah; Rizkiyah Amaliyah; Inayah Amalia; Yuninda Salva Shaffani (Penerbit Hellow Pustaka, 2025)
Background: The capacity of Human Resources (HR) in health and limited funding pose significant challenges to the sustainability of the Integrated Health Post (Posbindu) for Non-Communicable Diseases (NCDs) program in Klungkung Village, Sukorambi District. The success of this program heavily depends on the active role of health cadres and support from various parties. Although the Posbindu program has the potential to increase public awareness about NCD prevention through early detection, issues such as inadequate cadre training, insufficient facilities, and limited funding may hinder its effectiveness. This study aims to analyze strategies for strengthening the Posbindu NCD program in Klungkung Village by addressing factors that affect its sustainability. Method: This research uses a qualitative design with a case study approach. Data collection techniques involve in-depth interviews with key informants, including the Health Office, Puskesmas (community health center) staff, health cadres, and community members participating in the Posbindu program. Additionally, observations of Posbindu activities and documentation studies were conducted to obtain a comprehensive understanding of the program's implementation. Research Findings: The Posbindu NCD program in Klungkung Village has successfully attracted community members from various age groups. However, the number of cadres is limited, and the equipment available at each Posbindu varies. Cadres often do not receive adequate training, and funding for the Posbindu activities remains insufficient. These factors reduce the effectiveness of early NCD detection and prevention efforts conducted by the Posbindu in the village. Conclusion: To strengthen the implementation of the Posbindu NCD program in Klungkung Village, several strategies are necessary, including continuous training for cadres by health professionals, adding necessary equipment to support Posbindu activities, and increasing adequate funding to support program operations. Furthermore, intensified collaboration across sectors and active community participation are essential to ensure the program's sustainability. With these improvements, the Posbindu NCD program is expected to function more effectively in preventing and controlling NCDs in Klungkung Village.